Pulmonary Hypertension Complicating Connective Tissue Disease - Volkmann, Elizabeth R.; Chung, Augustine; Saggar, Rajan; Belperio, John A.; Lynch, Joseph P., III (Seminars in Respiratory and Critical Care Medicine, 2017)
Pulmonary hypertension (PH) may complicate connective tissue disease (CTD; particularly systemic sclerosis [scleroderma]), and is associated with increased mortality. More than 70% of cases of PH complicating CTD occur in patients with systemic sclerosis (SSc), which is the major focus of this article. Pulmonary complications (i.e., interstitial lung disease [ILD] and PH) are the leading causes of SSc-related deaths. “Isolated” PH (i.e., without ILD) complicates SSc in 7.5 to 20% of cases; secondary PH may also occur in patients with SSc-associated ILD. Several clinical markers and specific autoantibody profiles have been associated with PH in SSc. The role of PH-specific therapy in improving CTD-PH outcomes is under investigation, as prognosis and responsiveness to therapy appear to be worse in SSc-associated PH compared with idiopathic pulmonary arterial hypertension. We discuss medical therapies for CTD-associated PH and the role of lung transplantation for patients who fail medical therapy.
Keywords: systemic sclerosis; scleroderma; pulmonary hypertension; pulmonary arterial hypertension; connective tissue disease